A survey of current social network and online communication provision policies to support law enforcement identify offenders. (June 2017) - Horsman, Graeme
Abstract: Online forms of harassment, stalking and bullying on social network and communication platforms are now arguably wide-spread and subject to regular media coverage. As these provision continue to attract millions of users, generating significant volumes of traffic, regulating abuse and effectively reprimanding those who are involved in it, is a difficult and sometimes impossible task. This article collates information acquired from 22 popular social network and communication platforms in order to identify current regulatory gaps. Terms of service and privacy policies are reviewed to assess existing practices of data retention to evaluate the feasibility of law enforcement officials tracking those whose actions breach the law. For each provision, account sign-up processes are evaluated and policies for retaining Internet Protocol logs and user account information are assessed along with the availability of account preservation orders. Finally, recommendations are offered for improving current approaches to regulating social network crime and online offender tracking.